Pengaruh Pertumbuhan Penduduk dan Struktur Ekonomi Terhadap Pertumbuhan Ekonomi dan Pengangguran di Indonesia - Prana Cita, Kadek Fiba; Wirawan, I Gusti Putu Nata (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 10, Oktober 2016 (pp. 1011 - 1167), 2016)
This study aimed to determine the effect of population growth, economic structure directly to economic growth in Indonesia in 1995-2013, the effect of population growth, economic structure and economic growth directly against unemployment in Indonesia in 1995-2013, as well as the indirect effect of population growth and economic structure against unemployment through economic growth in Indonesia in 1995-2013. This study uses secondary data. The analysis technique used is the path analysis. Collecting data in this experiment was conducted using documentation. Based on the survey results revealed that population growth have positive and significant, while the structure of the economy have significant negative effect on economic growth in Indonesia on 1995-2013. Population growth have positive and significant effect on unemployment, while economic growth and economic structure have significant negative effect on unemployment in Indonesia on1995-2013. Economic growth is an intervening variable linking population growth and economic structure of the unemployed in Indonesia.
Keywords: Population Growth, Economic Structure, Economic Growth, Unemployment